Forced-Use Dust Bags for Management of External Parasites - Phillip E. Kaufman; Edwin R. Burgess; Emma N. I. Weeks (EDIS)
Dust bags are an effective method of horn fly and louse control. However, dust bags are only effective when hung in places where cattle are forced to use them. The best locations are areas where cattle must pass once or twice a day, or every other day, for instance between mineral boxes or water and pasture. During the field tests, forced-use dust bags provided an average of 90% horn fly control. Production was increased by an average of 34% over the normal management practice. This increase in production was equivalent to 1/3 lb/animal/day. This 5-page fact sheet was written by P. E. Kaufman and E. N. I. Weeks and originally published by the UF Department of Entomology and Nematology, November 2012. This version February 2022.